Identification and Expression Patterns of Anoplophora chinensis (Forster) Chemosensory Receptor Genes from the Antennal Transcriptome - Sun, Long; Zhang, Ya-Nan; Qian, Jia-Li; Kang, Ke; Zhang, Xiao-Qing; Deng, Jun-Dan; Tang, Yan-Ping; Chen, Cheng; Hansen, Laura; Xu, Tian; Zhang, Qing-He; Zhang, Long-Wa (Frontiers in Physiology, 2018)
The citrus long-horned beetle (CLB), Anoplophora chinensis (Forster) is a destructive native pest in China. Chemosensory receptors including odorant receptors (ORs), gustatory receptors (GRs) and ionotropic receptors (IRs) function to interface the insect with its chemical environment. In the current study, we assembled the antennal transcriptome of A. chinensis by next-generation sequencing. We assembled 44,938 unigenes from 64,787,784 clean reads and annotated their putative gene functions based on gene ontology (GO) and Clusters of Orthologous Groups of proteins (COG). Overall, 74 putative receptor genes from chemosensory receptor gene families, including 53 ORs, 17 GRs and 4 IRs were identified. Expression patterns of these receptors on the antennae, maxillary and labial palps, and remaining body segments of both male and female A. chinensis were performed using quantitative real time-PCR (RT-qPCR). The results revealed that 23 ORs, 6 GRs and 1 IR showed male-biased expression profiles, suggesting that they may play a significant role in sensing female-produced sex pheromones; whereas 8 ORs, 5 GRs and 1 IR showed female-biased expression profiles, indicating that these receptors may be involved in some female-specific behaviors such as oviposition site seeking. These results lay a solid foundation for deeply understanding CLB olfactory processing mechanisms. Moreover, by comparing our results with those from chemosensory receptor studies in other cerambycid species, several highly probable pheromone receptor candidates were highlighted, which may facilitate the identification of additional pheromone and/or host attractants in CLB.